Analysis of technical problems with destroying information stored on magnetic media. (1st January 2013) - Gärtner, M.; Kupfrian, J.; Möller, J.
In the present digital world, all information is stored on several types of media. The most prominent media used is the magnetic media also known as hard drive. Little or no effort is done to the increasing problem of secure destruction of information off these media. While the average user can afford the time and the implied security risk on using a software for deletion, corporates and governmental organisations alike cannot afford this. They need a faster and secure method of deleting the information on a hard drive. The paper will discuss possible economic and secure methods for data destruction as well as compare the methods.